A doubly distorted-wave method for atomic ionization by ultrashort laser pulses - Gravielle, Maria Silvia (2012)
We study a time-dependent distorted-wave formulation of atomic ionization by short laser pulses named the double-distorted Coulomb?Volkov (DDCV) approximation. The method takes into account the distortions introduced by the laser field in the initial and final channels, both by means of the Volkov phase. The DDCV model is applied to evaluate electron emissiondistributions for hydrogen atoms ionized by multi-cycle laser pulses. Results are comparedwith the predictions of an exact treatment based on the numerical solution of thetime-dependent Schr¨odinger equation (TDSE) and with values derived from the standard Coulomb?Volkov (CV) approach, considering different intensities and frequencies of the laser field. Good agreement with the TDSE solution has been obtained for laser frequencies higher than 0.1 au, extending the range of applicability of the usual CV-type methods.